Surface Plasmon Resonance Sensor of Toxic Nanoparticles in Aqueous Systems - Nasih Hma Salah (Eurasian Journal of Science and Engineering, 2019)
Given their potential antimicrobial activities, silver nanoparticles are utilised in various consumer goods, such as food packaging, medical devices, wound dressings, clothing, washing machines and refrigerators. However, despite the numerous advantages provided by silver nanoparticles, their use has been hindered by their potential human and environmental toxicity. For example, in rainbow trout, silver nanoparticles can drastically alter the functionality of vital organs, such as the liver, spleen and brain. The levels of silver nanoparticles in aquatic environments should be cautiously monitored to avoid their potential adverse on human health and aquatic organisms. Thus, in this study a sensor based on surface plasmon resonance (SPR) is developed for the rapid detection of trace existent of silver nanoparticles. The developed sensor can differentiate between colloidal silver and silver in solution (silver nitrate). Further analysis showed that, there was a significant difference between two results. The most striking observation to emerge from the data comparison was clearly observed.